Validation of an Oral Health–Related Quality of Life Measure for Cambodian Children - Turton, B.J.; Thomson, W.M.; Foster Page, L.A.; Saub, R.; Razak, I.A. (SAGE Publications (UK and US), 2015)
This study aimed to determine the impact of dental caries in terms of Oral Health-Related Quality of Life (OHRQoL) for Cambodian children. The Child Perceptions Questionnaires (CPQ) were cross-culturally adapted and validated for the Cambodian population using a sample of 430 Cambodian children. The participants had a high caries burden, with a mean number of decayed-missing-and-filled deciduous tooth surfaces (dmfs) of 8.8 (SD = 11.1) and a mean DMFS of 3.7 (SD = 5.5) for the permanent dentition. Two in 5 children had at least one pulpally involved tooth. There was a significant difference in mean CPQ8-10 and CPQ11-14 scores by caries experience and by global item response for the respective age-groups, with those in the more severe caries categories scoring higher. Similar gradients were apparent with the CPQ11-14 in the 8- to 10-year age-group. The differences in OHRQoL scores by caries experience demonstrate the construct validity of the CPQ11-14 for the 8- to 14-year age-group.